Chromochloris zofingiensis-Based Treatment of Whey Wastewater for Biorefinery Application: Biomass, Nutrient Removal, Astaxanthin and Lipid Production - Houria El Bakraoui; Amina Malaki; Miloudia Slaoui; Céline Laroche (Applied Sciences)
The dairy industry generates substantial quantities of wastewater, primarily whey wastewater, posing environmental challenges. Current treatment methods involve physical, chemical, and biological processes, but efficient solutions are still sought. Biological treatments using microalgae are gaining attention due to their potential to remove pollutants from wastewater and generate valuable products, making them an alternative way to improve environmental sustainability. The physicochemical characterization of whey effluents reveals a high organic content, an acidic pH, and elevated nutrient levels. This study investigates the potential of Chromochloris zofingiensis (formerly known as Chlorella zofingiensis) for treating whey wastewater using three concentrations, 10%, 20%, and 50%, over a 7-day culture period. The optimal concentration of whey wastewater for biomass, nutrient removal, astaxanthin, and lipid production was found to be 10%. At this concentration, C. zofingiensis achieved a biomass of 3.86 g L−1 and a removal efficiency of nutrients between 77.08% and 99.90%. Analysis of pigment production revealed decreases in chlorophyll and carotenoid production with increasing whey wastewater concentration, while lipid and astaxanthin production peaked at the 10% dilution. The chlorophyll a, chlorophyll b, total carotenoid, astaxanthin, and lipid contents were, respectively, 11.49 mg g−1, 4.56 mg g−1, 4.04 mg g−1, 0.71 mg g−1, and 30.49% in 10% whey wastewater. The fatty acid profiles indicated the predominance of saturated and unsaturated fatty acids, enhancing the biofuel potential of C. zofingiensis cultivated in whey wastewater. These findings demonstrate the dual benefit of using C. zofingiensis for sustainable whey wastewater treatment and high-value bioproduct generation, supporting the development of circular biorefinery systems.